Adrenal insufficiency in HIV/AIDS: a review. Issue 6 (2nd November 2021) - Mifsud, Simon; Gauci, Zachary; Gruppetta, Mark; Mallia Azzopardi, Charles; Fava, Stephen
ABSTRACT: Introduction: Adrenal insufficiency (AI) is one of the most common potentially life-threatening endocrine complications in people living with human immunodeficiency virus (PLHIV) infection and acquired immunodeficiency syndrome (AIDS). Areas covered: In this review, the authors explore the definitions of relative AI, primary AI, secondary AI and peripheral glucocorticoid resistance in PLHIV. It also focuses on the pathophysiology, etiology, diagnosis and management of this endocrinopathy in PLHIV. A literature review was conducted through Medline and Google Scholar search on the subject. Expert opinion: Physicians need to be aware of the endocrinological implications of HIV infection and its treatment, especially CYP3A4 enzyme inhibitors. A high index of clinical suspicion is needed in the detection of AI, especially in PLHIV, as it may present insidiously with nonspecific signs and symptoms and may be potentially life threatening if left untreated. Patients with overt primary and secondary AI require glucocorticoid replacement therapy. Overt primary AI also necessitates mineralocorticoid replacement. On the other hand, the management of relative AI remains controversial. In order to reduce the risk of adrenal crisis during periods of stress, the short-term use of glucocorticoids may be necessary in relative AI.